Does the DSN-MUI Fatwa on Cryptocurrency Affect Muslims' Investment Interest? - Apriyanto, Apriyanto; Laksono, Muflih Adi; Priyana, Yana (West Science Interdisciplinary Studies, 2025)
This study explores the impact of the DSN-MUI Fatwa on cryptocurrency on the investment interest of Muslims in Indonesia. Using a qualitative approach with five informants, the research examines their awareness, perceptions, and decision-making processes concerning cryptocurrency investments. The findings reveal that the Fatwa significantly influences investment decisions, primarily by emphasizing ethical concerns related to gharar (uncertainty) and riba (usury). While many investors adhere strictly to the Fatwa's guidance, others seek Sharia-compliant alternatives to participate in the cryptocurrency market. The study identifies key factors such as trust, perceived risks, and opportunities, highlighting a cautious yet growing interest in ethically aligned financial instruments. These findings provide valuable insights for Islamic financial institutions and regulators aiming to address the evolving needs of Muslim investors.